Estado nutricional de estudiantes de la Institución Educativa Enrique Cassinelli Chiappe del Distrito de La Esperanza, diciembre de 2016 - Aguilar Rodríguez, Carlos Neil (2017)
In the present study, the nutritional status of the students of the Educational Institution "Enrique Cassinelli Chiappe" of the District of La Esperanza, December 2016 was determined. For the determination, anthropometric measurements were used and for the interpretation of the anthropometric indicators weight / Age, height / age, body mass index / age and cephalic perimeter were used Z percentiles extracted from the World Health Organization. 71.4% of students present a normal weight for their age, while 4.0% is underweight and 24.6% is above normal weight for their age. 92.9% of students are of normal height for their age, while 4.8% are in malnutrition I and 2.4% in malnutrition II. 54.8% of students have normal body mass index (BMI) for their age, while 5.6% are underweight, 22.2% are overweight or obese, and 17.5% are overweight. 92% of students have a normal head circumference (PC), 5.6% have a higher PC and 2.4% have a lower PC. According to the results it was concluded that the highest percentage of children present a normal nutritional status in all parameters evaluated, however there are cases in a lower proportion of overweight, malnutrition, low height and low and high cephalic perimeter